Pengujian Monday Effect dan Weekend Effect Terhadap Return Saham Perusahaan di Jakarta Islamic Indeks (JII) Periode Sebelum dan Sesudah Covid - 19 - Tony Iswadi; Tuffahati Septia Nada; Riandy Mardhika Adif; Welhendra (Jurnal Informatika Ekonomi Bisnis, 2022)
Covid-19 is a pandemic event that has drastically affected the world economy, including activities that occur in the capital market. The existence of this pandemic period became the impetus to test the Monday Effect and Weekend Effect phenomena on Company Stock Returns in the Jakarta Islamic Index (JII) in the Period Before and After Covid-19. This study aims to determine the significant differences in stock returns that occurred between the Monday before Covid-19 and after Covid-19 on the Jakarta Islamic Index (JII). To find out the significant differences in stock returns that occurred between Fridays before Covid-19. This type of research is a quantitative approach; data collection method is a documentation technique; and the sampling method is purposive sampling technique. The analysis technique used is the Kolmogorov - Smirnov Normality Test, the Independent Sample t - Test, and the Kruskal Wallis Test. This study proves that there is a significant difference between stock returns on Monday before Covid 19 and stock returns on Friday after Covid 19. This can be seen from the significance value of 0.000 which is smaller than 0.05. There is a significant difference between stock returns on Monday before Covid-19 and stock returns on Friday after Covid-19. This can be seen from the significance value of 0.000 <0.05. So that this research can help in taking stock return policies.